Digital Marketing Strategies and Customer Engagement in Australia: An Interaction of Brand Trust and Consumer Literacy - Latif, Madiha (Business Review of Digital Revolution, 2025)
Digital transformation at a breakneck speed has disrupted customer engagement, and digital marketing strategies have become critical to driving consumer interactions. This study investigates the role of digital marketing strategies on customer engagement in Australia, with the moderation of brand trust and consumer digital literacy. Data from 330 Australian consumers were evaluated to test these relationships using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that digital marketing techniques encourage customers and validate the significance of digital channels in boosting customer involvement. It was found that brand trust and consumer digital literacy do not have a significant moderating effect on this relationship, indicating that consumer engagement with digital marketing is not strongly influenced by trust and the level of digital literacy, but rather by the content and attractiveness of the marketing efforts. This study adds to the body of knowledge regarding digital marketing effectiveness in emerging markets and offers practical implications for businesses and policymakers alike. The findings indicate that Australian companies should explore personalized and interactive digital strategies more closely while examining deeper drivers such as customer experience and perceived value that could bolster engagement.